The Efforts to preserve Javanese language at elementary school level in KKG Gugus Sakura Dabin IV Welahan District, Jepara - Raudhotul Jannah; Dwiana Asih Wiranti; Muhammad Misbahul Munir (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Indonesia is a country rich in cultural and linguistic diversity. Each region has its traditional language and literature, which are integral to the nation's cultural identity. The purpose of this study was to explore the various efforts made by Kelompok Kerja Guru (KKG) Gugus Sakura Dabin IV Welahan Jepara in preserving the Javanese language in elementary schools. By understanding the strategies and challenges faced, it is hoped that practical solutions can be found to maintain the sustainability of the Javanese language among the younger generation. This research method employs a descriptive qualitative approach. The subjects in this study were the KKG Gugus Sakura Dabin IV Welahan Jepara. The results of the study found seven efforts made by schools in preserving the Javanese language, namely the development of independent teaching modules by schools, the habituation of Javanese language days, talent and interest programs, student pre-competition guidance programs, the creation of Javanese script media, learning while playing, and finally the implementation of Javanese language training for teachers. The preservation of the Javanese language in the elementary schools of KKG Gugus Sakura is increasing through the efforts that have been implemented. Students are increasingly familiar with Javanese and apply it in their daily lives.